A review of the policy and regulatory environment of mobile banking in Zimbabwe - Tahwa, Felistas Sophie. (My University, 2014)
The dynamics in technology have ushered in innovative products such as mobile banking. It has been taken up by other economies such as Kenya, Philippines and others, each coming up with different results. The purpose of this qualitative research is to analyse and evaluate the impact of policy and regulation on the propagation of mobile banking generally but particularly in the Zimbabwe context. Findings of the research reveal a lack of articulate policy and regulation on m-banking, which has posed a challenge to the propagation of m-banking. While m-banking spans multiple domains, the research found that the respective stakeholders are currently working in isolation hence there is a need to work on co-jurisdiction. The outcome of the research shows there is currently no synergy in the awareness campaign drive and stakeholders are not willing to champion the drive. Other factors believed to contribute to the proliferation of m-banking have been identified as the restoration of customer confidence in the banking sector, a reduction of the cost of banking, a culture shift from a cash-centric economy to a non-cash culture and the addressing of intermittent electricity supply among others. The research also takes into consideration socio-economic factors that aid or hinder the rollout and effective uptake of the mobile banking service.
Thesis (M.M. (ICT Policy and Regulation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2013.
Keywords: Mobile banking; Zimbabwe